PENERAPAN ISO 9001.2008 TERHADAP KINERJA KEUANGAN PADA INDUSTRI KECIL DAN MENENGAH DI JAWA TIMUR - Himawan Adi Nugroho (Jurnal Ekonomi dan Bisnis Airlangga, 2018)
This research aims to find evidence whether the quality management system ISO 9001.2008 affect on financial performance (which variable were quick ratio, debt ratio, ROA and inventory turnover) a year before and a year after ISO 9001.2008 being applied in small and medium enterprises in East Java Region. The sample of this research were 46 small and medium enterprises in East Java Region that already had been certified The Quality Management System ISO 9001.2008 for the years of 2004 – 2010. This research is based on the quantitative approach by using wilcoxon signed ranks test enter method in SPSS program version 6.0. The result of this research indicates that quality management system ISO 9001.2008 had positive effect on quick ratio, debt ratio and ROA. While the other variable such as inventory turnover, ISO 9001.2008 have no positive effect on that variable.